Zum Hör-Seh-Verstehen von Video- und Fernsehsprach- programmen - LÖSCHMANN, Marianne (Wydawcnictwo Naukowe UAM, 1990)
The potential of sound films for foreign language learning and teaching can be fully realised only through modern technological developments. It is assume that the reception of video and TV foreign language programmes is a purposeful and mediating activity. The paper discusses the effect of various picture and sound forms, as «ell as the impact of the combinations of those forms that are relevant to the development of foreign language aural and visual comprehension. A theoretical model for the development of receptive skills has been developed in order to help overcome learning difficulties.